Flame Behavior During the Combustion of Premixed Kapok Oil Influenced by Oxygen and Magnetic Field - Dony Perdana; Muhamad Nur Rohman; Mochammad Khoirul Rosidin; Muhaji Muhaji (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study aimed to determine effect of oxygen enrichment and magnetic field direction on the flame behavior kapok oil combustion. Experiment was carried out to obtain flame evolution, temperature and height. Kapok oil (600 ml) was put in the boiler, and heated to 300°C. A burner chamber is placed for the reaction between kapok oil vapor with air from compressor and oxygen. Two permanent magnets of neodymium nickel grade N52 with intensity 1.1 Tesla were placed on side of burner tip. Results showed the magnetic field produce more transparent, slimmer flames with highest temperature of 679°C, lowest flames height of 5 mm. Magnetic fields produce a Lorentz force that breaks the fuel chemical chain and creates magnetic pulses in the flames. Oxygen contained in air around the burner coupled with oxygen enrichment create excessive oxidizing gas to separate and release electrons. Excessive oxygen results in a higher flame temperature due to faster combustion reaction. The magnetic fields around flames induces flow air which magnetically cause heat transfer around the flame, resulted variable flame height. This combustion produces different flame evolution, temperature, and height. Keywords: Flames behavior, Flames colour, Kapok oil, Magnetic field, Premixed combustion.